2013
DOI: 10.1088/0026-1394/50/3/257
|View full text |Cite
|
Sign up to set email alerts
|

The European Comparison of Absolute Gravimeters 2011 (ECAG-2011) in Walferdange, Luxembourg: results and recommendations

Abstract: 19 Lantmäteriet-the Swedish mapping, cadastral and land registration, Sweden

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(25 citation statements)
references
References 11 publications
2
23
0
Order By: Relevance
“…[, ], or included in the uncertainty budget [ Sato et al ., ; Mémin et al ., ; Palinkas et al ., ]. Intercomparison campaigns [e.g., Francis et al ., , , , ; Jiang et al ., ; Schmerge et al ., ; Vitushkin et al ., ] showed that differences between FG5 and JILAg gravimeters are commonly of the order of 100–150 nm/s 2 . A difference as large as 461 nm/s 2 was reported for one of the A10 instruments that participated in the ICAG‐2001 intercomparison [ Vitushkin et al ., ].…”
Section: Instrumental Artifactsmentioning
confidence: 99%
See 2 more Smart Citations
“…[, ], or included in the uncertainty budget [ Sato et al ., ; Mémin et al ., ; Palinkas et al ., ]. Intercomparison campaigns [e.g., Francis et al ., , , , ; Jiang et al ., ; Schmerge et al ., ; Vitushkin et al ., ] showed that differences between FG5 and JILAg gravimeters are commonly of the order of 100–150 nm/s 2 . A difference as large as 461 nm/s 2 was reported for one of the A10 instruments that participated in the ICAG‐2001 intercomparison [ Vitushkin et al ., ].…”
Section: Instrumental Artifactsmentioning
confidence: 99%
“…A difference as large as 461 nm/s 2 was reported for one of the A10 instruments that participated in the ICAG‐2001 intercomparison [ Vitushkin et al ., ]. In other comparisons, systematic and random errors of A10 gravimeters ranged between 70 and 220 nm/s 2 [ Jiang et al ., ; Francis et al ., , , ].…”
Section: Instrumental Artifactsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 5 also take into account the results of calibration of absolute gravimeters presented as part of ICAG2011 (Francis at al., 2013), therefore the values of g are at a level which is in compliance with what is defined as the European level of reference.…”
Section: Geodynamic Studies In the Pieniny Klippen Belt In 2004-2015mentioning
confidence: 99%
“…Calculating the half difference between these two measurements, one gets the shift due to Coriolis acceleration and averaging the two measurements, the interferometer phase is corrected from Coriolis acceleration. We use this last method in [3], as well as during comparison campaigns [6,13,14].…”
Section: Introductionmentioning
confidence: 99%